Building brand value the Playboy way - Gunelius, Susan (Basingstoke, Hampshire : Palgrave MacMillan, 2009)
'Susan Gunelius uncovers how a brand about sex survived and thrived despite attacks from every direction, in an increasingly competitive market and jaded consumers. It's the story of brand building, brand value, brand longevity and the ultimate brand champion'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Playboy Enterprises; Branding (Marketing) -- United States; Target marketing -- United States